Marketing Strategy for Six Nine Footwear in Purpose to Increase Sales - Venina, Cut Anggun; Aldianto, Leo (The Indonesian Journal of Business Administration, 2015)
Abstract.The development of internet has grown very rapidly that has become an important part in the of today's modern life. Sixnine as one of the SMEs sees the opportunity of rapid development of technology today, and it makes Sixnine think to start an online business. Sixnine offers products which are specific shoes for men with three models of shoes, i.e boots, casual and semi-formal. Sixnine makes its sales through social media, which causeSixnine has more than one social media, its website, facebook, twitter, and instragram. Sixnine has established for nearly two and a half years, and along with the times Sixnine has faced some kind of issues, i.e the low sales in Bandung, the great number of competitors and it can not handle orders in a timely manner. With those issues, various forms of external and internal analysis are performed such as Porter's Five Forces, SWOT analysis, Marketing Mix, STP, and Customer Perception of Service. In scientific works, some surveys also have been performed which aims to determine the awareness level of Sixnine’s brand and products, satisfaction with the Sixnine’s products and lifestyle of Bandung citizens As results, there are two main issues focused in this study, i.e the low level of public awareness of Sixnine’s brand and products and unstructured work division, these issues affect the lower sales. For solutions, there are several things that must be considered to increase the level of public awareness toward the Sixnine’s products and brand which must be accompanied by well planned marketing strategy, i.e change the Sixnine’s tagline, join exhibitions or fairs, distribute flyers during the bazaar, maintenance of social media and endorsement of local actress. As for handling the unstructured work division, it must perform re-structure the company by adding new employees to handle social media and recap the data of good reservation. Those strategies should be implemented and well planned as it will affect the increase of Sixnine’s product sales Action plan and implementation are formed for Sixnine commencing from November 2014 to April 2015. Action plan and its implementation, will describe more detail about the timing of any action plan that has been set for Sixnine. Keywords: Footwear, internet, marketing strategies, brand awareness, social media